Методи забезпечення надійності газовідвідних трактів котлів ТЕС - Шелешей, Тетяна Вікторівна (НТУ "ХПІ", 2017)
Ерозійно-корозійні пошкодження елементів енергообладнання є однією з основних причин порушення нормальної експлуатації, а іноді і зупинка теплоенергетичного обладнання. При спалюванні газу конденсат містить розчинені оксиди вуглецю, азоту і оксиди сірки, що призводить до корозії і ерозії внутрішніх поверхонь газоходів котла. Для виконання умови відвернення утворення конденсату необхідно підвищувати температуру внутрішньої поверхні газовідвідного тракту tп або зменшувати вологість димових газів і таким чином знижувати температуру їхньої точки роси tр. В даній роботі наведені технологічні напрямки утилізації димових газів без конденсації водяної пари.

Erosion and corrosion damage of the elements of electric equipment is one of the main reasons for the normal operation disturbance and sometimes lockup of the thermal power equipment. The metal loss in the elements of power plants due to the erosion and corrosion wear over their entire service life exceeds 8 % of the original mass that results in the efficiency reduction. In addition, erosion and corrosion process products cause the blockage of water-steam circuit which negatively affects a reliable operation of the power equipment. The purpose of this research was to study the influence of the temperature of dew point on the reliability control. The domestic literature describes some relationships used for the definition of sulfuric acid dew point that were obtained using the dust firing technique. This method allows for the computation of temperature differences and the method showed that that temperature of sulfuric acid dew point exceeds that of the dew point of pure vapors (tр = 45–54 °С). To meet a condition of the prevention of condensate formation it is necessary to increase the temperature of the internal surface of gas bleeding circuit ts and decrease the humidity of furnace gases and thus decrease the temperature of their dew point tр. The technological areas of the disposal of furnace gases with no water steam condensation include the heat transfer to the water in the additional heating surface; additional heat transfer to the blow air through an increase in the temperature difference due to a decrease in the temperature of entering air, and the additional heat transfer to the feed water in available heating surfaces.
The methods used to provide the reliability of gas bleeding ducts for EPP boilers
Keywords: температура точки роси; температура відхідних газів; поверхні нагріву; корозія; ерозія; dew point temperature; emitted gas temperature; heating surface